Photosensibilisierte O2-Übertragung in Gegenwart oder mittels β-Carotin unter Ausschluß von Singulett-Sauerstoff - G.O. Schenck; G. Schade (CHIMIA)
Carotenoids and vitamin A may react as sensitizers, substrates, quenchers and scavengers in photo- and autooxidation processes. β-Carotene has been shown to act as sensitizer in type 2 photooxygenation of dienes and olefins generating singlet oxygen (1O2) in the Kautsky-Schenck mechanism via excited carotene-O2 complexes. Strong quenching of 1O2 by β-carotene has been found especially occuring in solvents containing benzene as applied by Foote and Denny, but not in methanol or isopropanol, etc. 1O2-Quenching appears to be associated with oxygenation of β-carotene and is interpreted as catalytic action via complexing of 1O2 with β-carotene. The difference in behavior of the excited sensitizer-oxygen-complexes and of the quencher/acceptor-oxygen-complexes is explained by the different states of aggregation of the β-carotenes in various solvents. Association e.g. in alcohols appears favouring sensitization, whereas stronger solvation by benzene is favouring acceptor and associated catalytic or quenching activities. The problem of solvation of 1O2 needs further consideration.